But Why Can't I? - A Book About Rules - Sue Graves (Bharat Franklin Watts, 2011)
Children sometimes find it hard to follow rules. This encouraging book joins Noah and his babysitter, Jenny, who shows him how rules help keep people safe, healthy, and happy. But Why Can't I? is part of the Our Emotions and Behavior series.The Our Emotions and Behavior series uses cheerful brightly illustrated stories to help kids understand how their emotions and actions are related$1 (Band how they can learn to manage both. At the end of each book, a two-page series of pictures invites kids to tell a story in their own words. A special section for adults suggests discussion questions and ideas for guiding children to talk about their feelings.s
Keywords: Nonfiction -- Nonfiction